Principles of marketing. - Open Textbook Library; BC Open Textbook Project; BCcampus (University of Minnesota Libraries Publishing, 2015)
"Principles of Marketing teaches the experience and process of actually doing marketing - not just the vocabulary. It carries five dominant themes throughout in order to expose students to marketing in today's environment."--Open Textbook Library.
What is marketing? -- Strategic planning -- Consumer behavior : how people make buying decisions -- Business buying behavior -- Market segmenting, targeting, and positioning -- Creating offerings -- Developing and managing offerings -- Using marketing channels to create value for customers -- Using supply chains to create value for customers -- Gathering and using information : marketing research and market intelligence -- Integrated marketing communications and the changing media landscape -- Public relations, social media and sponsorships -- Professional selling -- Customer satisfaction, loyalty, and empowerment -- Price, the only revenue generator -- The marketing plan.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
Principles of Marketing by [Author removed at request of original publisher] is licensed under a Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License, except where otherwise noted.--title page verso.
Author removed at request of original publisher. This edition adapted from a work originally produced in 2010 by a publisher who has requested that it not receive attribution.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
Online version, 2015 edition; title from PDF (viewed on July 26, 2016).
Keywords: Marketing; Electronic books